Comparing outcomes of early, late, and non-surgical management of intraspinal abscess. (February 2017) - Farber, S. Harrison; Murphy, Kelly R.; Suryadevara, Carter M.; Babu, Ranjith; Yang, Siyun; Feng, Liqi; Xie, Jichun; Perfect, John R.; Lad, Shivanand P.
Highlights: Intraspinal abscess is a rare disease not easily studied in a randomized setting. This is the largest study of this rare disease to our knowledge (>10, 000 patients). The prevalence of ISA more than doubled between 2003–2012. Neurologic deficits appear to drive earlier surgical intervention. Costs and LOS were decreased when surgery was performed in the first 48 hours. Abstract: Intraspinal abscesses (ISAs) are rare lesions that are often neurologically devastating. Current treatment paradigms vary widely including early surgical decompression, drainage, and systemic antibiotics, delayed surgery, and sole medical management. The National Inpatient Sample (NIS) database was queried for cases of ISA from 2003 to 2012. Early and late surgery were defined as occurring before or after 48 h of admission. Outcome measures included mortality, incidence of major complications, length of stay (LOS), and inpatient costs. A total of 10, 150 patients were included (6281 early surgery, 3167 delayed surgery, 702 medical management). Paralysis, the main comorbidity, was most associated with early surgery ( p  < 0.0001). In multivariate analysis, the rates of postoperative infection and paraplegia were highest with early surgery ( p  < 0.0001), but the incidence of sepsis was higher with delayed surgery ( p  < 0.0001). Early surgery was least associated with in-hospital mortality ( p  = 0.0212), sepsis ( p  < 0.001), and had the shortest LOS ( p  < 0.001). Charges were highest with delayed surgery, and least with medical management ( p  < 0.001). Medical management was associated with lower rates of complications ( p  < 0.001). This is the largest study of patients with ISAs ever performed. Our results suggest that patients with ISAs undergoing surgical management have better outcomes and lower costs when operated on within 48 h of admission, emphasizing the importance of accurate and early diagnosis of ISA.